2016
DOI: 10.1073/pnas.1522325113
|View full text |Cite
|
Sign up to set email alerts
|

Strand-biased cytosine deamination at the replication fork causes cytosine to thymine mutations in Escherichia coli

Abstract: The rate of cytosine deamination is much higher in single-stranded DNA (ssDNA) than in double-stranded DNA, and copying the resulting uracils causes C to T mutations. To study this phenomenon, the catalytic domain of APOBEC3G (A3G-CTD), an ssDNA-specific cytosine deaminase, was expressed in an Escherichia coli strain defective in uracil repair (ung mutant), and the mutations that accumulated over thousands of generations were determined by whole-genome sequencing. C:G to T:A transitions dominated, with signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 63 publications
9
90
0
Order By: Relevance
“…22 The ssDNA at replication forks has been suggested as an additional substrate that is susceptible to APOBEC3 deamination based on recent data from genome sequencing analyses 32,33 and model organism systems. 30,31 These studies point to the potential for APOBEC3 enzymes to deaminate various cellular substrates, however the capacity for A3A to damage ssDNA during replication has not been previously demonstrated in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…22 The ssDNA at replication forks has been suggested as an additional substrate that is susceptible to APOBEC3 deamination based on recent data from genome sequencing analyses 32,33 and model organism systems. 30,31 These studies point to the potential for APOBEC3 enzymes to deaminate various cellular substrates, however the capacity for A3A to damage ssDNA during replication has not been previously demonstrated in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was under review, several groups published complementary data suggesting APOBEC3 deamination of ssDNA at replication forks in various computational examinations of tumor genome sequences 32,33 and model organism evaluations utilizing ectopic APO-BEC3 expression. 30,31 Notably, Hoopes, et al demonstrated preferential deamination of the lagging strand template in replicating yeast exposed to human A3A and A3B. 31 These findings were echoed in a genome sequence analysis of E. coli by Bhagwat, et al following exposure to the C-terminal deaminase domain of A3G over many generations of replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6E). The latter is supported by several recent studies investigating the nature of APOBEC-mediated mutations in various cancers (36)(37)(38)(39). However, considering the gene organization of the BKPyV genome and the bidirectional nature of its genome replication, we cannot at this time definitively determine whether transcription or lagging-strand DNA replication predisposes to more viral genomic mutation.…”
Section: Figmentioning
confidence: 92%